Revision of the Metallactus kollari species-group with a new diagnosis of the genus (Coleoptera: Chrysomelidae: Cryptocephalinae) - Sassi, Davide (Zootaxa, 2018)
The genus Metallactus has been controversial since its introduction due to the ambiguous nature of the original diagnosis. This has caused some confusion in the taxonomy of Neotropical Pachybrachina. In this work the morphology of endophallus, which is useful for the characterization of species groups in several groups of Coleoptera, including Cryptocephalinae, has been analyzed. This has proven to be a good resource also in the taxonomic treatment of the species belonging to the genus Metallactus. After a careful survey on most of the species described so far, the endophallus shape in Metallactus turned out to be remarkably distinctive and very promising in the delimitation of species groups. The present work includes: a) a new diagnosis of the genus Metallactus on the basis of the aedeagal anatomy; b) the designation of the type species of the nominal genus; c) the revision of a first species-group of the genus, including the type species, hereinafter called Metallactus kollari species-group. Before this revision, catalogues had been reporting 13 species attributable to this group, in the present work three species have been synonymized and seven have been described as new to science. Therefore, the group includes 17 species. The species described as new are: Metallactus rileyi n. sp., M. bellatrix n. sp., M. longicornis n. sp.; M. londonpridei n. sp., M. regalini n. sp., M. bezoar n. sp., M. guarani n. sp. The new synonymies are as follows: Metallactus albipes Suffrian, 1866 (= M. nigrofasciatus Suffrian, 1866 n. syn.), M. albifrons Suffrian, 1866 (= M. flavofrontalis Jacoby, 1907 n. syn.), M. dodecastictus Suffrian, 1866 (= Griburius nigritarsis Jacoby, 1907 n. syn.). The lectotypes of all previously described species have been designated. The new synonymies, the name-bearing type fixations and designations and the nomenclatural acts have been critically discussed. An identification key for the species-group is also provided.